Competing first-price and second-price auctions - J.M.J. Delnoij; Kris De Jaegher (Utrecht University, Utrecht School of Economics, Tjalling C. Koopmans Research Institute, 2016)
This paper theoretically investigates which auctions competing sellers select when they can choose between first-price and second-price auctions, and when risk averse bidders endogenously enter one of the auctions. We first consider bidders' entry decisions between exogenously given auctions, and find that there exists a symmetric entry equilibrium that is characterized by a mixed strategy, which depends on the bidders' degree of absolute risk aversion. In a next step, we endogenize the sellers' choice of auctions. We show that competing sellers have a dominant strategy to select first-price auctions if bidders exhibit nondecreasing absolute risk aversion. If bidders exhibit decreasing absolute risk aversion, however, other equilibria exist in which sellers select second-price auctions as well.
Keywords: 330; Auctions; Entry decisions; Risk aversion